Utilizing public private partnership (PPP) in the diffusion of the internet for all - Pangalangan, Francesco; Imbang, Glen (Quezon City University of the Philippines Diliman, 2017)
Public Private Partnership (PPP) brings together two key actors in the innovation system, the government, and industry, in a collaboration that can result in the diffusion of innovation. This paper studies the experience of various cases from around the globe wherein PPP was successfully used to diffuse the use of Internet as an innovation at both the regional and national level, to the social and economic benefit of societies there. Through a forecast by analogy and analysis, this paper further seeks to identify challenges and derive recommendations for the successful implementation of a National Broadband Plan through the PPP model, here in the Philippines.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Public-private sector cooperation